Innovation and change at Ardmona - Image Link; Video Education Australasia (Australia : Video Education Australasia, 1998)
As the fruit canning industry undergone major in recent decades. Ardmona has been one of the few survivors. It is because a company which embraced change, especially in the 1990s. In the face of severe competition due to globalisation, technological change and changes in consumer needs, Ardmona has worked hard to maintain its position as an industry leader. At Ardmona exporting is now a major activity, product innovation is critical, path-breaking information technology has been developed, and a change in the culture of the staff has underspinned all other changes
Title from title screen
Executive producer, Neil Barrett
NArration: John Pemberton
DVD format
Keywords: Ardmona; Organizational change -- Management; Product management; Technological innovations -- Economic aspects; Personnel management -- Australia -- Case studies; Product management -- Australia -- Case studies